The diversity of education in pathology worldwide and perspectives of the international academy of pathology - Kontogeorgos, George (Pathologia, 2020)
The article, based on the personal experience of the President of the International Academy of Pathology (IAP), presents the features of three main training programs for pathologists: European, Anglo-Saxon and North-American, applied in accordance with the guidelines of the European Union of Medical Professionals (UEMS), the Royal College of Pathologists (RCPath) and the American Board of Pathology (ABPath), respectively. Differences in the training of pathologists in different countries are associated with the structure and time of training, the possibilities of financing it, the sub-specialties of pathologists and their accreditation by the commissions for pathology. The minimum training time for pathologists varies in different countries of the world and is: six years (in Sri Lanka), five and a half years (in the countries of the British Commonwealth), four years (in the USA, North American countries, EU countries, Norway, Switzerland, Turkey, Australia, New Zealand), three to five years (in South Africa), two years (in Russia, Armenia, Mongolia, Vietnam, Cambodia), one year (in Ukraine). The structure of training for resident pathologists is also different. For example, the European system of training pathologists covers such compulsory subjects as clinical and surgical pathology, autopsy, cytopathology, as well as additional (for some sub-specialties) educational disciplines: neuropathology, dermatopathology, pediatric pathology. The Anglo-Saxon system, in addition to clinical and surgical pathology, includes chemical pathology (metabolic medicine), virology, infectious diseases, and optional subjects: hematopathology and biochemistry. Medical microbiology and chemical pathology are also being studied in Arab countries. The North American resident pathologist training system includes surgical pathology, autopsy, forensic medical examination, chemistry, cytopathology, cytogenetics, molecular diagnostics, hematopathology, dermatopathology, neuropathology, virology, infectious diseases, liver pathology, transplant pathology, transfusion medicine. The financial support provided by the Education Committee of the IAP encourages the development of educational programs and the creation of schools in pathology in developing countries, the organization of international Congresses, teleconferences and webinars, and the development of the international program “Goodwill / Visiting / Ambassador”. In conclusion, Albert Einstein’s statement is given: “Education is not the learning of facts, but the training of the mind to think”. Conclusion. The time has come for an educational revolution. It is necessary to give strength to everyone in order to open channels everywhere to improve education and achieve harmonization of Pathology globally.